(untitled) (INNOVATIVE ECONOMY, 2020)
Lomonosova O.E. PLANNING OF WORK OF SCIENTIFIC AND PEDAGOGICAL WORKERS IN THE CONTEXT OF FULFILMENT OF NORMATIVE REQUIREMENTS TO THE LEVEL OF THEIR SCIENTIFIC AND PROFESSIONAL ACTIVITY Purpose. The aim of the article is the development of proposals for improving the planning of the activities of scientific and pedagogical workers in order to continuously provide them with regulatory requirements to the level of scientific and professional activity. Methodology of research. Planning activity of scientific and pedagogical workers is proposed to be implemented on the basis of the method of sliding scheduling in the form of plans-charts. The application of this method enables to realize the most important principles of planning – continuity and flexibility, and to ensure continuous monitoring of the implementation of planned activities. Findings. It is determined that, it is advisable to formulate plans-schedules of measures, implementation of which ensures the continuous fulfilment of requirements aimed at achieving the necessary number of types and results of activities that are stipulated by the licensing conditions for conducting educational activities in the field of higher education in order to maintain the normative level of scientific and professional activity of scientific and pedagogical workers. The form of the plan-chart is developed as the main document in which the planning of measures is implemented and the control over their fulfilment is carried out. It also clearly shows, at the expense of which exactly the results and activities will be ensured by scientific and pedagogical staff normative requirements to the level of their scientific and professional activity in the planned and several subsequent years. Scientific novelty. For the first time, the task of developing the toolkit for planning the activities of scientific and pedagogical workers has been set and solved, taking into account the need to maintain their normative level of scientific and professional activity. Practical significance. The developed method of planning the activity of scientific and pedagogical workers on the basis of schedule-graphs without refinement can be applied in any institution of higher education of Ukraine. Key words: institutions of higher education; scientific and pedagogical workers; work of scientific and pedagogical workers; planning of scientific and pedagogical workers; scientific and professional activity of scientific and pedagogical workers.